2019
DOI: 10.1039/c9fo00515c
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of extracts of red and yellow fruits of cornelian cherries (Cornus mas L.) on rats with streptozotocin-induced diabetes mellitus

Abstract: The effects of extracts of red and yellow fruits of cornelian cherries have been evaluated in rats with streptozotocin-induced diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 52 publications
7
67
1
2
Order By: Relevance
“…Identification of compounds was achieved using the Acquity ultra-performance liquid chromatography (UPLC) system, paired with a quadrupole-time of flight (Q-TOF) MS instrument (UPLC/Synapt Q-TOF MS, Waters Corp., Milford, MA, USA), with an electrospray ionization (ESI) source [6]. The separation was performed on an Acquity BEH C18 column (100 mm × 2.1 mm i.d., 1.7 µm; Waters Corp., Milford, MA, USA).…”
Section: Identification Of Compounds By Liquid Chromatography-mass Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of compounds was achieved using the Acquity ultra-performance liquid chromatography (UPLC) system, paired with a quadrupole-time of flight (Q-TOF) MS instrument (UPLC/Synapt Q-TOF MS, Waters Corp., Milford, MA, USA), with an electrospray ionization (ESI) source [6]. The separation was performed on an Acquity BEH C18 column (100 mm × 2.1 mm i.d., 1.7 µm; Waters Corp., Milford, MA, USA).…”
Section: Identification Of Compounds By Liquid Chromatography-mass Spmentioning
confidence: 99%
“…In our previous research, we found antidiabetic and antioxidant effects of cornelian cherry (Cornus mas L.) extracts in rats with experimental diabetes [6]. Extracts of red and yellow fruits of cornelian cherry contain iridoids in significant amounts (73.5% and 88.2%, respectively) and one of its main iridoid glycosides is loganic acid (LA).…”
Section: Introductionmentioning
confidence: 99%
“…The hypoglycemic activity of PTA is indicated by its suppression of fasting blood glucose levels, enhancement of glucose tolerance, and recovery in serum levels of GHbA1c and insulin. Hyperglycemia causes an increase in protein glycosylation, leading to an increase of glycated hemoglobin [31]. Once the oxygen carrying capacity of hemoglobin is reduced, the over-production of ROS results and is responsible for organ hypoxia in patients with diabetes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Flavanoller (kateşin, epikateşin ve polimerik prosiyanidin) genotipe bağlı olarak farklı oranlarda bulunurlar 23 . Kızılcıkta da epikateşin en bol bulunan flavanol olup 32 kateşin, proantosiyanin içerirken 32,33 kuarsetin 3glukuronit, kuersetin 3-glukozit, kuersetin 3-ramnoz yaygın olarak bulunan flavonoid gruplarıdır [34][35][36] .…”
Section: Flavonoid Ve Flavanollerunclassified
“…Yukarıda bahsedilen biyoaktif bileşenler dışında, yüksek oranda C vitamini içermekte olan bu gruptaki meyveler, β karoten, A vitamini, E vitamini ile potasyum başta olmak üzere mineral açısından da oldukça zenginlerdir 23,36,37 39,40,42,[48][49][50] , anti-inflamatuar 43,44,[46][47][48][49] , anti diyabetik 54,55 , hipolipidemik 16,[53][54][55] , artrit ve endotelyal disfonksiyon 43,57,58 ile hipertansiyon [60][61][62] üzerine pozitif etki…”
Section: Flavonoid Ve Flavanollerunclassified